Analisis Faktor-faktor Optimalisasi Laba Bersih: Studi Kasus pada PT. Indofood Sukses Makmur Tbk di Jakarta - Aulia Isnaini Hasanah; Tjandra Wasesa; Heri Toni Hendro P; Wiratna Wiratna; Diana Zuhroh (Jurnal Mahasiswa Manajemen dan Akuntansi, 2024)
This research was conducted at PT. Indofood Sukses Makmur Tbk which is located in Jakarta. This research aims to identify and analyze factors and efforts in optimizing net profit. This research is qualitative research with a descriptive approach. This research uses documentation as a procedure for collecting data. The conclusion obtained from this research is that the factors that influence the optimization of PT's net profit Indofood Sukses Makmur Tbk is sales and costs. Where, sales are one of the revenues for the company which can increase the optimization of net profit. Meanwhile, costs that can influence the optimization of a company's net profit are all costs incurred by the company. Meanwhile, efforts can be made to optimize net profit by PT Indofood Sukses Makmur Tbk is by increasing sales and controlling the costs incurred by the company, especially costs which continue to experience high increases from year to year.